RESEARCH INTO 3D PRINTING LAYER ADHESION IN ABS MATERIALS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The purpose of this article is to determine the impact of the two factors – layer thickness and printing speed in the adhesion of the layers in the ABS polymer. ABS control test tubes were printed and the tensile strength of each tube was measured. By means of statistical analysis, it was determined the impact of the layer thickness and the print speed on the adhesion between the layers. The research was focused on one of the most used materials in 3D printing. It can be concluded from the obtained results that the layer thickness has the greatest impact on the adhesion.